Streptococcus bovis/gallolyticus induce the development of colorectal cancer. - Abdulamir, Ahmed Sahib; Hafidh, Rand Riadh; Abu Bakar , Fatimah (In Tech, 2012)
The role, of microbial agents and the infection of the intestinal mucosa in the carcinogenesis, or the development of colorectal cancer (CRC) is one of the hot topics in the field of CRC where much research has been done. However, this topic has long been underestimated by most of the related books. This chapter is intended to cover the relationship of CRC development with bacteria implicated in the development of CRC such as S. bovis, S. gallolyticus, S. equines, S. infantarius, E .coli, C. difficile…etc. However, S. gallolyticus and S. bovis will be discussed thoroughly in this chapter as they are considered the prototype for intestinal microorganisms related to CRC and colorectal premalignant lesions.